Topical Colloidal Silver for the Treatment of Recalcitrant Chronic Rhinosinusitis - Ooi, Mian L.; Richter, Katharina; Bennett, Catherine; Macias-Valle, Luis; Vreugde, Sarah; Psaltis, Alkis J.; Wormald, Peter-John (Frontiers in Microbiology, 2018)
BACKGROUND: The management of recalcitrant chronic rhinosinusitis (CRS) is challenged by difficult-to- treat polymicrobial biofilms and multidrug resistant bacteria. This has led to the search for broad-spectrum non-antibiotic antimicrobial therapies. Colloidal silver (CS) has significant antibiofilm activity in vitro and in vivo against S. aureus, MRSA and P. aeruginosa. However, due to the lack of scientific efficacy, it is only currently used as an alternative medicine. This is the first study looking at the safety and efficacy of colloidal silver in recalcitrant CRS. METHODS: Patients were included when they had previously undergone endoscopic sinus surgery and presented with signs and symptoms of sinus infection with positive bacterial cultures. 22 patients completed the study. Patients were allocated to 10-14 days of culture- directed oral antibiotics with twice daily saline rinses (n=11) or 10 days of twice daily 0.015mg/mL colloidal silver rinses (n=11). Safety observations included pre- and post- treatment serum silver levels, University of Pennsylvania Smell Identification Test (UPSIT) and adverse event (AE) reporting. Efficacy was assessed comparing microbiology results, Lund Kennedy Scores (LKS) and symptom scores using Visual Analogue Scale (VAS) and Sino-Nasal Outcome Test (SNOT-22). RESULTS: CS demonstrated good safety profile with no major adverse events, no changes in UPSIT and transient serum silver level changes in 4 patients. CS patients had 1/11 (9.09%) negative cultures, compared to 2/11 (18.18%) in the control group upon completion of the study. Whilst not statistically significant, both groups showed similar improvement in symptoms and endoscopic scores. CONCLUSION: This study concludes that twice daily CS (0.015mg/mL) sinonasal rinses for 10 days is safe but not superior to culture-directed oral antibiotics. Further studies including more patients and looking at longer treatment or improving the tonicity of the solution for better tolerability should be explored.